Effects of participation level and physical activity on eating behavior and disordered eating symptoms in the Brazilian version of the New Moves intervention: data from a cluster randomized controlled trial - Dunker, Karin Louise Lenz; Alvarenga, Marle dos Santos; Teixeira, Paula Costa; Grigolon, Ruth Bartelli (São Paulo Medical Journal, 2021)
BACKGROUND: Childhood and adolescent obesity is a worldwide public health concern. The New Moves program aims to change eating behavior (EB) and physical activity (PA). OBJECTIVE: To evaluate the effectiveness of an intervention and predictors of better outcomes relating to EB and PA levels. DESIGN AND SETTING: Secondary data from a cluster randomized controlled trial in 10 public schools in São Paulo, Brazil. METHODS: 270 female adolescents, aged 12 to 14 years, were analyzed. Participation levels were categorized as presence in 1 to 9 sessions or 10 to 17 sessions, or control. Effectiveness was evaluated through improvement in disordered EB (DEB) and EB. Predictors of better outcomes relating to PA levels were evaluated through clustering of individual characteristics that affected changes in PA scores. RESULTS: Participation level was not significantly associated with changes in DEB or EB. Girls with higher body mass index percentile (BMI-P) percentile tended to have increases in sedentary lifestyles through the program. Girls with less body image dissatisfaction presented higher increases in daily PA. Girls with higher BMI-P percentile and higher self-esteem showed reductions in sedentary lifestyles. The program seemed to have more effect on daily PA among older girls than among younger girls. CONCLUSIONS: This program could be used as a structured action plan in schools, with the aims of improving eating behaviors and physical activity, in addition to promoting self-acceptance. The results indicate the importance of evaluating determinants of adherence, as these metrics might influence the effectiveness and future design of lifestyle programs. BRAZILIAN REGISTRY OF CLINICAL TRIALS: RBR-6ddpb3.